Engaging Airmen with Cyber Education and Training: Designing a Platform Using Gamification (Journal of The Colloquium for Information Systems Security Education, 2019)
Several issues have impeded the effectiveness of United States Air Force cyber education and training in terms of ensuring that enough Airmen at all different levels of cyber education and training are appropriately prepared. The framework proposed in ‘Rethinking USAF Cyber Education and Training' [1] is a response to this issue. The framework suggests a platform built around the idea of crowd-sourced content, community engagement, and feedback. This paper proposes several ideas of implementing gamification and human-focused design concepts on the platform and includes an analysis of how this can affect Airmen at different tiers of cyber development. Ideas relating to social involvement, introducing non-cyber-experts to the platform, and a navigable cyber topic map are proposed. These ideas are only a subset of the foundational concepts that can be applied to the platform; data from the platform should be used to continuously tailor the platform to maximize user engagement and consequently users' cyber knowledge.
Keywords: cyber education and training; gamification; human-focused design; topic map; 21st century learning